Peran Japan Foundation Dalam Menjalankan Diplomasi Kebudayaan Jepang Di Indonesia Tahun 2015-2018 - Aprilliyanto, Ammar fu’ad; Purwanto, Adi Joko (Kajian Hubungan Internasional, 2022)
This research aims to determine how the Japan Foundation's role in carrying out Japanese cultural diplomacy in Indonesia in 2015-2018. As a result of colonial events in the past, Japan wanted to change its negative image in the eyes of the Indonesian people, besides that they conducted cultural diplomacy as well as to achieve their national interests. Therefore to launch the diplomacy process they formed the Japan Foundation in Indonesia.                                                                                 The research method used in this study is a qualitative method that is descriptive and analytical. This method seeks to describe the situation based on existing realities and is supported by theories and concepts that are used in order to be able to describe research precisely the nature, circumstances and symptoms, as well as supported by literature study, and online search. Theoretical foundation used is role theory.  The results of this research indicate that the Japan Foundation has a significant role in fulfilling Japan's national interests. The role of the Japan Foundation as an Instrument for the Exchange of Art and Culture, as a Place for Japanese Language Education and Learning, as a Japanese Study Group and Intellectual Exchange creates an understanding between the people of Japan and the people of Indonesia so that it becomes an important factor in the development of diplomatic relations between Japan and Indonesia. So it can be concluded that the Japan Foundation is an important part of Japan's success in implementing the country's cultural diplomacy in Indonesia.